FACTORS CONTRIBUTING TO THE WOMEN’S STRUGGLE FOR THE POSITION AS LEGISLATORS IN BALI PROVINCE - Sukiada, I Nyoman (E-Journal of Cultural Studies, 2016)
Since the reformation era competition for the position as legislators has been getting open to women. Different Acts have been issued to increase the women’s representation in the legislature. Although the women’s representation in the legislature in Bali Province has not achieved the 30% target, the attempts made by women to be legislators should be appreciated. The reason is that such attempts can accelerate the gender equality in politics. This present study is intended to understand and describe the factors contributing to the women’s struggle for the position as legislators. The study used the critical theory and the descriptive qualitative theory. The data were obtained through observation and in-depth interview. The result of the study shows that women had competed for the position as legislators; however, the legislature was still dominated by men. This cannot be separated from the women’s collective habitus which has been formed through their interaction with the Balinese society’s objective structure as can be seen from the social, political, cultural,socio-economic and globalization realities.
Keywords: Balinese women, reformation era, collective habitus, globalization